Desvelando a arte na cidade de belo horizonte pela educação do olhar: sequência didática para alunos do Ensino Médio - Atiná Aguiar Pinter Cordeiro (2016)
This work aims through Teaching Sequence methodology works education look with students of the 3rd year of high school in a municipal school of Belo Horizonte with 4 (four) museums circuit option Museums Circuit Artistic Cultural Heritage of Belo Horizonte. With exercises look at the language of photography, film and artistic productions, logbooks and portfolios in the way of superimposed layers allowing the development of "education look" of high school students. For "Education Look" happened were developed several products such as: portfolios of the three participating classes, visitation itineraries for museums, parental authorization for students to participate, guidelines for the development of artistic activities, guidelines for the making of the logbooks, guidance for the filming of the sculptures in the city, postcard creation to evaluative return of logbooks and mounting the exhibition as devolutiva.